UV Spectrophotometric Determination of Drotaverine Hydrochloride in Bulk and Pharmaceutical Formulation - DAHIVELKAR, P.P.; BARI, S.B.; SHIRKHEDKAR, A.A. (Asian Journal of Chemistry, 2010)
A simple, sensitive and reproducible UV spectrophotometric method for the determination of drotaverine hydrochloride in bulk samples and pharmaceutical formulations was developed. The maximum absorbance observed was at 241 nm in methanol. Beer's law was followed in the concentration range of 04-32 μg/mL.